FIRST- ORDER STRONG DIFFERENTIAL SUBORDINATION AND SUPERORDINATION PROPERTIES FOR ANALYTIC FUNCTIONS ASSOCIATED WITH LINEAR OPERATOR - Alhadithi, Abdul (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In the present paper we study of some properties first - order strong differential subordination and superordination for analytic functions associated with Ruscheweyh derivative operator which are obtained by considering suitable classes of admissible functions.